2000
DOI: 10.1128/aem.66.6.2658-2663.2000
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobitoxine Production by Bradyrhizobium elkanii Enhances Nodulation and Competitiveness on Macroptilium atropurpureum

Abstract: Application of 1-aminoocyclopropane-1-carboxylic acid, an ethylene precursor, decreased nodulation of Macroptilium atropurpureum by Bradyrhizobium elkanii. B. elkanii produces rhizobitoxine, an ethylene synthesis inhibitor. Elimination of rhizobitoxine production in B. elkanii increased ethylene evolution and decreased nodulation and competitiveness on M. atropurpureum. These results suggest that rhizobitoxine enhances nodulation and competitiveness of B. elkanii on M. atropurpureum.The symbiotic interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 38 publications
1
71
1
2
Order By: Relevance
“…However, in contrast to other work (Yuhashi et al, 2000;Okazaki et al, 2003), we found that Rtx( þ ) rhizobia were no more competitive than were Rtx(À), founding only 42% of nodules (t ¼ 0.84, P ¼ 0.42, d.f. ¼ 10, two-sided t-test) during co-inoculation.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…However, in contrast to other work (Yuhashi et al, 2000;Okazaki et al, 2003), we found that Rtx( þ ) rhizobia were no more competitive than were Rtx(À), founding only 42% of nodules (t ¼ 0.84, P ¼ 0.42, d.f. ¼ 10, two-sided t-test) during co-inoculation.…”
Section: Resultscontrasting
confidence: 55%
“…Some rhizobia make the ethylene inhibitor, rhizobitoxine (Rtx), which increases nodules per plant and competitiveness for nodule formation (Duodu et al, 1999;Yuhashi et al, 2000;Okazaki et al, 2003). Increasing the number of nodules formed by a plant will not increase an Rtx strain's relative fitness (proportional representation in the population) unless Rtx rhizobia are disproportionately represented in the additional nodules, but other fitness benefits are possible.…”
Section: Introductionmentioning
confidence: 99%
“…PCR results indicate that this gene cluster is present in all 39 sampled S. medicae strains. In B. elkanii, rhizobitoxine has been shown to enhance nodulation capabilities of the bacteria by inhibiting ethylene synthesis in plant tissues (Yuhashi et al, 2000). If the rtx homologues of S. medicae encode the same function, the strains we collected might have an increased capability to induce nodules on the roots of their host when compared with S. medicae WSM 419.…”
Section: Discussionmentioning
confidence: 99%
“…4C) and competitively (Fig. 4D), indicating that the induced ACC deaminase gene enhances nodulation and competitiveness in a manner similar to rhizobitoxine, a bradyrhizobial inhibitor of ACC synthase (26,44,45).…”
Section: Vol 186 2004mentioning
confidence: 99%